Hippos are huge! - London, Jonathan, 1947- (Candlewick Press, 2015)
Overview: Hippos may make you laugh, but watch out! An acclaimed naturalist takes an exuberant look at these massive, swift, and super dangerous animals. What's the deadliest animal in Africa? It's not the lion or the crocodile-it's the hippopotamus! Hippos have razor-sharp tusks, weigh as much as fifty men, and can run twenty-five miles per hour! Follow these hefty hulks as they glide underwater, play tug-of-war, swat balls of dung at one another, and nuzzle their young in the mud. Just don't get too close-they could chomp you in two!